Development of Social Enterprises in Thailand: A Critical Investigation of the Social Enterprise Promotion Act 2019 within a Theoretical Framework of Law and Development - Prateeppornnarong, Dhiyathad; Nuchpiam, Prapin (NIDA Development Journal, 2022)
From 2000 onwards, social enterprises (SEs) are growing in number in several countries around the world (e.g. United Kingdom, South Korea, Singapore). In some countries, legislation was passed to ensure the promotion of SEs as well as their good governance. This paper adopts qualitative methodology to investigate the role of law in promoting the development of SEs. It contributes theoretically by adopting a general theory of law and development established by Yong-Shik Lee for analysing how the introduction of SE law in general, and the enforcement of the Social Enterprise Promotion Act (SEPA) of Thailand in particular, may pose challenges to the development of SEs. From the perspective of the general theory of law and development, the “regulatory impact mechanisms” comprising of ‘regulatory design,’ ‘regulatory compliance,’ and ‘quality of implementation’ are of crucial importance for achieving desirable outcomes, particularly sustainable development. Distilled from the theory, we argue that the key challenges of Thailand’s SEPA in facilitating development of SEs in the country are consisted of the issues on regulatory design and quality of implementation.